EFFICIENCY ANALYSIS OF INDONESIAN TAX OFFICES - Kurniawan Panji Laksono; Diah Widyawati (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2018)
This research studies the technical efficiency of Tax Offices (KPP) in Indonesia by applying stochastic frontier analysis model. Observation was in the form of data aggregation at the level of province to all Tax Offices in Indonesia, besides those within the scopes of the Large Taxpayer Regional Office and Jakarta Special Regional Offices for approximately seven years (from 2010 to 2016). Results of the analysis show different rates of technical efficiency in inter-provinces taxation. Analysis on the efficiency determinants reveals a number of internal factors contributing to the technical efficiency of taxation, like the audit effort and external factors, such as community education level. Increase on these two can improve the efficiency and productivity of tax offices.